Uncertainty, Pedagogical Imagination, Explorative Reasoning, Social Justice, and Critique - Skovsmose, Ole [UNESP]; Mukhopadhyay, S.; Greer, B. (Mathematics Education & Soc, 2015)
It is autumn 2014. Well, actually it is not. It is springtime, because as I write this I am in Brazil, preparing my talk for the Eighth International Mathematics Education and Society conference (MES8). I was really happy to receive the invitation to make this talk. I was here in the very beginning, giving a Plenary in MESI in Nottingham in 1998. In my talk this time I will address the question: What could critical mathematics education mean for different groups of students? I am not going to argue for distinguishing between critical mathematics education and mathematics education for social justice. I believe we are dealing with two largely overlapping educational approaches. So the title of my talk could just as well be: What could mathematics education for social justice mean for different groups of students? The text I am presenting here, however, is not the text for my talk. Instead in this paper, I address some philosophical issues that might only appear implicitly in my talk. Specifically, here I will reflect on the notions of uncertainty, pedagogical imagination, explorative reasoning, social justice, and critique.